Studi Awal Sintesis dan Karakterisasi Bi(Pb)-Sr-Ca-Cu-O dengan Penambahan Carbon Nanotube dan TiO2 Menggunakan Metoda Reaksi Padatan dan Proses Sintering Berulang [Preliminary Study Synthesis and Characterization of Bi(Pb)-Sr-Ca-Cu-O By Addition of Carbon Nanotube and TiO2 Using Solid Reaction Method and Recurrent Sintering Process] - Rizki Syahfina; Bintoro Siswayanti; Sigit Dwi Yudanto; Agung Imaduddin; Nurul Suhada; Fauzan Amri; Mukti Hamjah Harahap (Metalurgi, 2017)
Bi1.6Pb0.4Sr2Ca2Cu3O10+δ with the addition of carbon nanotubes (CNT) and TiO2 have been synthesized using solid state reaction method with the repeated sintering process. 0.1 wt % of CNT and 5 wt% of TiO2 have been added to analyze the effect on the synthesizing of 2223 phases. The samples were analyzed using XRD (X-ray diffractometer) and SEM (Scanning Electron Microscopy). Based on the XRD results, 2223 and 2212 were formed. The addition of CNTs and TiO2 reduced the intensity of 2223 phases. This is due to the addition of CNTs and TiO2 as an impurity and prevent the formation of the phases. Also, the repeated sintering process led to the increase of 2223 phase, and the decrease of 2212 phase. However, the repeated sintering process in the B-CNT and B-TiO samples eliminates the impurities phase thus increasing the volume fraction 2223 and decreasing the volume fraction 2212. Based on morphological structure through SEM observation, the addition of CNT in the Bi(Pb)-2223 samples formed longer plates with large porosity spaces while the addition of TiO2 formed clumps on the Bi(Pb)-2223 morphological structure. However, the repeated sintering process improves the morphological structure of B-CNT and B-TiO becomes increasingly denser and the smaller porosity space.AbstrakTelah dilakukan sintesis Bi1,6Pb0,4Sr2Ca2Cu3O10+δ dengan penambahan CNT (carbon nanotube) dan penambahan TiO2 menggunakan metode reaksi padatan dengan proses sintering berulang. Penambahan CNT sebesar 0,1 %berat dan TiO2 sebesar 5 %berat dan sintering berulang dilakukan untuk mempelajari pengaruhnya terhadap pembentukan fasa 2223 beserta pengotornya, dan mempelajari perubahan morfologi Bi1,6Pb0,4Sr2Ca2Cu3O10+δ. Bi1,6Pb0,4Sr2Ca2Cu3O10+δ yang dibuat dianalisis dengan XRD (x-ray diffractometer) dan SEM (scanning electron microscopy). Berdasarkan hasil XRD, penambahan 0,1 %berat CNT dan TiO2 sebesar 5 %berat pada superkonduktor Bi(Pb)-2223 diketahui menghasilkan fasa 2223, fasa 2212, dan juga fasa pengotor. Namun proses sintering berulang mampu mengurangi fasa impuritas, meningkatkan fraksi volume 2223, serta menurunkan fraksi volume 2212.   Berdasarkan pengamatan struktur morfologi melalui SEM, penambahan CNT pada superkonduktor Bi(Pb)-2223 membentuk serpihan memanjang dengan ruang porositas yang besar sedangkan penambahan TiO2 membentuk gumpalan pada struktur morfologi Bi(Pb)-2223. Proses sintering berulang mampu memperbaiki struktur morfologi B-CNT dan B-TiO menjadi semakin rapat dan ruang porositas yang semakin kecil.